Long-Term Spatiotemporal Variation in the Juvenile Fish Assemblage of the Tramandaí River Estuary (29°S) and Adjacent Coast in Southern Brazil - Vieira, João; Román-Robles, Verónica; Rodrigues, Fábio; Ramos, Lisiane; dos Santos, Mauricio Lang (Frontiers in Marine Science, 2019)
Based on a set of intermittent and seasonal data, covering a discontinuous 21-year period (1995 to 2016) and using a standard beach seine with replicates at several collection points inside the Tramandaí River estuary (TRE) and outside in the marine adjacent coastal area (MACA), we evaluated connectivity between TRE and MACA and the spatiotemporal variations of fish associations. In the TRE (405 samples; 42,987 individuals) 55 species were captured. In the MACA (297 samples; 54,295 individuals) 41 species were captured. After data standardization the expected richness of the TRE [E(S) = 18.2] was significantly greater (p <0.05) than that of the MACA [E(S) = 14.4]. The fish association structure and distribution patterns in TRE and MACA are dynamic and interconnected but quite different in terms of species composition, especially due to the influence of local salinity. The TRE association is richer in a number of species but numerically dominated by marine estuarine-dependent juveniles. Freshwater species may eventually be carried in by heavy rains, bringing pulses of species richness. The MACA association is represented by a few typical marine species in addition to a couple of estuarine-related transient species who uses the surf-zone as a passageway to enter the estuaries. Even if there is a higher percentage of common species reported (30 out of 66), the monthly average Jaccard Index of similarity (JI = 28%) and the monthly average Percent Similarity Index (PSI=30%) was low, suggesting that the shallow water functional connectivity between MACA and TRE are represented by few species that occur equally in abundance in both environments. Juvenile of two species of mullets (Mugil liza and Mugil curema) add up to more than 70% of the total catches in both environments. The hypothesized signal of decadal diversity and abundance reduction seems to be muffled by seasonal environmental fluctuation revealing that fish assemblage of MACA and TRE are highly resilient through the years. The only observed interdecadal trend was the reduction in abundance of juvenile M. liza that seems to parallel the reduction in abundance of the adults fishing stocks in southern Brazil.